Sex differences in content and structural characteristics of emotional intelligence in the period of adolescence - Khonski, Sergei I. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The paper presents results of empirical research of sex differences in emotional intelligence among individuals in the period of adolescence. The author combines trait and ability measures of emotional intelligence. The essential components and structures of male and female adolescents’ emotional intelligence were established and compared. The correlation between trait and ability emotional intelligence are described separately for male and female adolescents. The author gives different arguments explaining causes of results.
Keywords: emotional intelligence; content characteristics of emotional intelligence; structural characteristics of emotional intelligence; sex differences